2020
DOI: 10.1049/mna2.12019
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐MgO prepared via templating on biodegradable filter paper

Abstract: Nano‐MgO was successfully fabricated by a facile, inexpensive, and environment‐friendly synthetic method using filter paper as a bio‐template. The influence of the concentration of raw material Mg(CH3COO)2·4H2O on the textural properties of nano‐MgO was investigated, and the as‐prepared nano‐MgO was characterized by X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, energy dispersive X‐ray analysis, thermo gravimetric analysis, Fourier transform infrared spectroscopy. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Various biomaterials have been subjected in the metal oxide adsorbent fabrication phase, such as eggshell membrane, flower petals, fruit peel, fibrous cotton wool, leaves, filter paper, etc [19-21, 12, 10]. According to previous research, the utilisation of biomaterial templating (bio-templating) has demonstrated strategic fabrication routes for the metal oxide adsorbent, particularly MgO, with enhanced physicochemical properties, which has significantly improved the adsorption performance of the MgO [19,12,10,22]. Considering the potential beneficial effect of fibrous biomaterial in developing hierarchicalstructured adsorbent, a cellulosic filter paper material has been reported to be a promising candidate [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various biomaterials have been subjected in the metal oxide adsorbent fabrication phase, such as eggshell membrane, flower petals, fruit peel, fibrous cotton wool, leaves, filter paper, etc [19-21, 12, 10]. According to previous research, the utilisation of biomaterial templating (bio-templating) has demonstrated strategic fabrication routes for the metal oxide adsorbent, particularly MgO, with enhanced physicochemical properties, which has significantly improved the adsorption performance of the MgO [19,12,10,22]. Considering the potential beneficial effect of fibrous biomaterial in developing hierarchicalstructured adsorbent, a cellulosic filter paper material has been reported to be a promising candidate [19].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research, the utilisation of biomaterial templating (bio-templating) has demonstrated strategic fabrication routes for the metal oxide adsorbent, particularly MgO, with enhanced physicochemical properties, which has significantly improved the adsorption performance of the MgO [19,12,10,22]. Considering the potential beneficial effect of fibrous biomaterial in developing hierarchicalstructured adsorbent, a cellulosic filter paper material has been reported to be a promising candidate [19]. According to the study reported by Chen et al, filter paper-templated MgO adsorbent fabricated using magnesium acetate and ethanol as precursor and preparation growth medium, respectively, has resulted to the MgO with nano-shaped structure with filter paper induced fibrous morphological features [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are several methods for synthesizing MgO nanomaterials with different morphologies. 15–23 MgO nanostructures were synthesized on a Si substrate via thermal evaporation using Mg powder as the raw material. Nanocubes with edge lengths of 0.5–5 μm and nanowires with diameters of 20–60 nm were obtained when a mixture of Ar and O 2 was introduced, while polyhedral shells and nanotubes were acquired under a H 2 atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…17 MgO fibres with a width of approximately 100 nm were fabricated through templating on biodegradable filter paper, which is composed of small particles with an average size of 20 nm. 18 MgO nano-flakes were synthesized by a green route with a crystallite size of 20–25 nm. 19 Three kinds of MgO nanostructures including nanowires, nanobelts and nanotubes were synthesized on a Si substrate in the temperature range of 580–670 °C, using Sn as the catalyst by the chemical vapor deposition (CVD) route.…”
Section: Introductionmentioning
confidence: 99%